Cigarette smoking, disease severity and autoantibody expression in African Americans with recent-onset rheumatoid arthritis. Issue 11 (15th January 2008) - Mikuls, T R; Hughes, L B; Westfall, A O; Holers, V M; Parrish, L; van der Heijde, D; van Everdingen, M; Alarcón, G S; Conn, D L; Jonas, B; Callahan, L F; Smith, E A; et al.
Abstract : Objective: To examine the association of smoking with clinical and serological features in African Americans with recent-onset rheumatoid arthritis (RA) and to explore whether this association is dependent on the presence of the HLA-DRB1 shared epitope (SE). Methods: In African Americans with recent-onset RA (n = 300), we examined the association of cigarette smoking (current versus past versus never and pack-years of exposure) with anti-cyclic citrullinated peptide antibody, rheumatoid factor (RF) (IgM and IgA), rheumatoid nodules and baseline radiographic erosions using logistic and cumulative logistic regression (adjusting for SE status). We also examined for evidence of interaction between smoking status and SE for all outcomes. Results: Although there was no association with RF-IgA seropositivity, current smokers were approximately twice as likely as never smokers to have higher IgA-RF concentrations (based on tertiles; OR = 1.74; 95% CI 1.05 to 2.88) and nodules (OR = 2.43; 95% CI 1.13 to 5.22). These associations were most pronounced in those with more than 20 pack-years of exposure. There was no association of smoking status or cumulative tobacco exposure with anti-cyclic citrullinated peptide antibody, IgM-RF or radiographic erosions. There was also no evidence of a biological or statistical SE–smoking interaction for any of the outcomes examined. Conclusions: This is the first study to systematically examine the association of cigarette smoking with RA-related features in African Americans. Cigarette smoking is associated with both subcutaneous nodules and higher serum concentrations of IgA-RF in African Americans with RA, associations that may have important implications for long-term outcomes in this population.